2014
DOI: 10.1530/endoabs.34.p229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treatment with Liraglutide on atherothrombotic risk in obese young women with polycystic ovary syndrome and controls

Abstract: Background: Polycystic ovary syndrome (PCOS) is associated with obesity and increased cardiovascular (CV) risk markers. In this study our aim was to assess the effects of six months treatment with liraglutide 1.8 mg od on obesity, and CV risk markers, particularly platelet function, in young obese women with PCOS compared to controls of similar age and weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Parameters of clotting and platelet function were also evaluated before and after 6 months of liraglutide (1.8 mg daily) therapy in obese, non-diabetic women with and without polycystic ovary syndrome (Kahal et al, 2015). P-selectin expression, fibrinogen, or platelet fibrinogen binding levels and platelet aggregation responses to ADP (0.1-10 mM) or the prostacyclin PGI 2 (1-100 nM) were not different after 6 months of liraglutide administration.…”
Section: Thrombosis and Platelet Aggregationmentioning
confidence: 99%
“…Parameters of clotting and platelet function were also evaluated before and after 6 months of liraglutide (1.8 mg daily) therapy in obese, non-diabetic women with and without polycystic ovary syndrome (Kahal et al, 2015). P-selectin expression, fibrinogen, or platelet fibrinogen binding levels and platelet aggregation responses to ADP (0.1-10 mM) or the prostacyclin PGI 2 (1-100 nM) were not different after 6 months of liraglutide administration.…”
Section: Thrombosis and Platelet Aggregationmentioning
confidence: 99%
“…Glucagon‐like peptide 1 receptor agonists (GLP‐1RA) cause weight loss in patients with T2D and obesity, and have been tested in PCOS in smaller studies . None of these studies was placebo‐controlled, and often metformin was allowed as a pre‐ or co‐medication.…”
Section: Introductionmentioning
confidence: 99%
“…35 Uncontrolled studies also reported reductions in weight, waist circumference and visceral adipose tissue after treatment with liraglutide 1.2-1.8 mg od. [36][37][38][39] A reduction in urinary isoprostanes, a marker of oxidative stress, and hsCRP levels was also observed in patients treated with liraglutide. 38,39 Interestingly, platelet activation was reduced and serum levels of P-selectin, intercellular adhesion molecule-1 and vascular cell adhesion molecule-1, which are markers of endothelial dysfunction, decreased after treatment with liraglutide for 6 months but no effect on carotid intima-media thickness was observed.…”
Section: Liraglutidementioning
confidence: 88%
“…[36][37][38][39] A reduction in urinary isoprostanes, a marker of oxidative stress, and hsCRP levels was also observed in patients treated with liraglutide. 38,39 Interestingly, platelet activation was reduced and serum levels of P-selectin, intercellular adhesion molecule-1 and vascular cell adhesion molecule-1, which are markers of endothelial dysfunction, decreased after treatment with liraglutide for 6 months but no effect on carotid intima-media thickness was observed. 38 Liraglutide also reduced serum levels of procollagen type 3 amino-terminal peptide, a marker of liver fi brosis.…”
Section: Liraglutidementioning
confidence: 88%
See 1 more Smart Citation